Where lung cancer and tuberculosis intersect: recent advances - Fang, Chunju; He, Xuanlu; Tang, Fei; Wang, Zi; Pan, Cong; Zhang, Qi; Wu, Jing; Wang, Qinglan; Liu, Daishun; Zhang, Yu (Frontiers in Immunology, 2025)
Lung cancer (LC) and tuberculosis (TB) represent two major global public health issues. Prior evidence has suggested a link between TB infection and an increased risk of LC. As advancements in LC treatment have led to extended survival rates for LC patients, the co-occurrence of TB and LC has grown more prevalent and poses novel clinical challenges. The intricate molecular mechanisms connecting TB and LC are closely intertwined and many issues remain to be addressed. This review focuses on resemblance between the immunosuppression in tumor and granuloma microenvironments, exploring immunometabolism, cell plasticity, inflammatory signaling pathways, microbiomics, and up-to-date information derived from spatial multi-omics between TB and LC. Furthermore, we outline immunization-related molecular mechanisms underlying these two diseases and propose future research directions. By discussing recent advances and potential targets, this review aims to establish a foundation for developing future therapeutic strategies targeting LC with concurrent TB infection.